2015
DOI: 10.1016/j.adolescence.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Borderline personality symptoms and perceived caregiver criticism in adolescents

Abstract: Despite findings of an association between adolescent psychopathology and perceived parental criticism, the relation between adolescent borderline personality disorder (BPD) symptoms and perceived parental criticism has not been examined. Given the centrality of interpersonal sensitivity to BPD (relative to other forms of psychopathology), we hypothesized that adolescent BPD symptoms would be uniquely related to perceived caregiver criticism, above and beyond other forms of psychopathology and general emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Also in clinical samples, adolescents and young adults with BPD report that their parents displayed several problematic parenting practices (e.g. emotional withdrawal, parental inconsistencies, invalidation of thoughts and feelings; [7,10,14,46,63,80,89,91]. Studies investigating child-driven effects have focused on temperament-related features: a review of Boucher et al [14] summarized that parents of children with BPD often describe their child as "unusually sensitive" or with a "difficult temperament" early on.…”
Section: Caregiver-child Interactions and Bpdmentioning
confidence: 99%
“…Also in clinical samples, adolescents and young adults with BPD report that their parents displayed several problematic parenting practices (e.g. emotional withdrawal, parental inconsistencies, invalidation of thoughts and feelings; [7,10,14,46,63,80,89,91]. Studies investigating child-driven effects have focused on temperament-related features: a review of Boucher et al [14] summarized that parents of children with BPD often describe their child as "unusually sensitive" or with a "difficult temperament" early on.…”
Section: Caregiver-child Interactions and Bpdmentioning
confidence: 99%
“…As a result, patients anticipate that they cannot rely on others for assistance. Adolescent BPD risk factors include a history of disrupted attachment, maternal neglect, maternal rejection, grossly inappropriate parental behavior, number of mother and father surrogates, physical and sexual abuse, parental loss [17], perceived caregiver criticism [18], and low socioeconomic status [19]. These elements lend support to an insecure attachment etiological model.…”
Section: Etiologymentioning
confidence: 99%
“…A genetic predisposition to interpersonal hypersensitivity is assumed to interact with negative relational experiences such as punitive behaviors of parents during the child's early development, resulting in relational deficits at a later age. One study examined the relationship of BPD symptoms with perceptions of caregiver criticism in a high-risk sample of 109 adolescents in a residential psychiatric treatment facility [21]. Findings suggested that adolescents with BPD symptoms may perceive their caregivers as more critical even if their caregivers do not actually exhibit high levels of criticism.…”
Section: Maladaptive Parentingmentioning
confidence: 99%